Proceedings of the 5th Workshop on Argument Mining 2018
DOI: 10.18653/v1/w18-5218
|View full text |Cite
|
Sign up to set email alerts
|

More or less controlled elicitation of argumentative text: Enlarging a microtext corpus via crowdsourcing

Abstract: We present an extension of an annotated corpus of short argumentative texts that had originally been built in a controlled text production experiment. Our extension more than doubles the size of the corpus by means of crowdsourcing. We report on the setup of this experiment and on the consequences that crowdsourcing had for assembling the data, and in particular for annotation. We labeled the argumentative structure by marking claims, premises, and relations between them, following the scheme used in the origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 13 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…The volume of data, particularly data annotated at the most fine grained level, is still far below what would be required to apply many of the techniques previously discussed in a domain independent manner. Attempts are being made to overcome this lack of data, including the use of crowdsourced annotation (Ghosh et al 2014;Skeppstedt, Peldszus, and Stede 2018) and automatic methods to extend the data currently annotated (Bilu, Hershcovich, and Slonim 2015). As these efforts combine with increasing attention to manual analysis, the volume of data available should increase rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…The volume of data, particularly data annotated at the most fine grained level, is still far below what would be required to apply many of the techniques previously discussed in a domain independent manner. Attempts are being made to overcome this lack of data, including the use of crowdsourced annotation (Ghosh et al 2014;Skeppstedt, Peldszus, and Stede 2018) and automatic methods to extend the data currently annotated (Bilu, Hershcovich, and Slonim 2015). As these efforts combine with increasing attention to manual analysis, the volume of data available should increase rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Fishcheva and Kotelnikov [7] showed that the machine translation of the English-language Argumentative Microtext Corpus (ArgMicro) [24], [27] into Russian allows obtaining the performance of ADUs classification that is not inferior to human translation. In this paper, following [7], we investigate the possibility of improving the performance of ADUs classification based on the extension of the Russian version of the ArgMicro corpus through machine translation of the Persuasive Essays Corpus (PersEssays) [29].…”
Section: Introductionmentioning
confidence: 99%
“…Materials and Methods4.1 Text corporaWithin this study, we used the Argumentative Microtext Corpus (ArgMicro)[24],[27] and the Persuasive Essay Corpus (PersEssays)[29]. Fishcheva and Kotelnikov[7] showed that the best result among…”
mentioning
confidence: 99%
“…We noticed that in many cases, the major claim is restated in the conclusion section of an essay, summing up the entire argument. Skeppstedt et al (2018) also noticed this and coined the name RESTATEMENT to model this phenomenon. In our scheme, the RESTATEMENT relation holds between two sentences if the second one repeats high-level argument material that has been previously described by the first, without adding a new idea into the discourse.…”
Section: Restatementmentioning
confidence: 96%